Rancang Bangun Sistem Informasi Perpustakaan SMA Negeri 1 Sreseh Sampang Berbasis Website Dengan Metode Rad - Fais Irwanda; Agussalim Agussalim; Abdul Rezha Efrat Najaf (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
Currently, the development of information technology has advanced in all sectors, one of which is the education sector which plays an important role in optimizing library functions and services in educational institutions. SMA Negeri 1 Sreseh Sampang developed a library information system to increase effectiveness and accessibility in managing libraries. System development was carried out using a RAD approach, including workshops on requirements planning, design and implementation. During implementation, the system utilizes a web platform compiled with the Laravel framework and MySQL database. The results of this research show that the library information system of SMA Negeri 1 Sreseh Sampang can cover all library business needs and can be used by all library members and employees, so that information can be presented more quickly and efficiently.